Intelligent spectacle and interactive interference for cultural sustainability via research-creation - Zhao, Jie; Dalal, Sanghamitra; Abu Bakar, Mohd Syuhaidi; Wan Yahaya, Wan Aida (Faculty of Art and Design, 2025)
Media ecology characterized by intelligence and interaction has emerged as a critical platform for sustainable cultural communication in digital being. This evolving field integrates various forms of media to facilitate the preservation and communication of cultural values in an increasingly interconnected world. The domain of art design, particularly through digital animation, experienced a transformative milestone since 2020s' with the rise of Artificial Intelligence Generated Content (AIGC) as a phenomenon-level spectacle in media ecology. AIGC not only signifies a shift towards technology-driven creativity but also heralds new paradigms in artistic expression and audience engagement. Interactive animation plays a pivotal role in this context, serving as a bridge between the languages of art and technology, from sophisticated game engines to immersive art installations. It enables creators to convey complex messages and emotions, fostering deeper connections with audiences across different cultural backgrounds. While the interplay of interaction and interference fosters artistic innovation, it also presents significant challenges to traditional media communication models and the principles of cultural sustainability. The dynamic nature of intelligent interactions can disrupt established cultural narratives, leading to both opportunities for novel expressions and dilemmas regarding the authenticity and continuity of cultural heritage. This article adopts research-creation as methodology, a mixed-methods approach via academic analyses with creative artwork, predominantly qualitative research supplemented by case studies and quantitative survey questionnaires, to explore these impacts. By integrating diverse research techniques, the communication study aims to provide a comprehensive understanding of how interactive technologies influence the preservation and evolution of cultural expressions, which delves into the balance between embracing technological advancements and maintaining cultural integrity, seeking strategies that promote sustainable cultural practices in the face of rapid digital transformation. Through this exploration, the article contributes to the ongoing meditation on balancing tradition and innovation within the dynamic environment of digital media ecology.